Catastrophe Containment and Relief Trust-Third Tranche Of Debt Service Relief In The Context Of The COVID-19 Pandemic. (Policy Papers; Policy Paper, 2021)
This paper proposes that the Executive Board approve the disbursement of a third tranche of CCRT debt service relief to 28 of the 29 CCRT-eligible members, covering the period April 14, 2021 through October 15, 2021, given staff's assessment that sufficient financial resources are available.